Making our ideas clear : pragmatism in psychoanalysis - Rosenbaum, Philip (Advances in cultural psychology., 2015)
This book brings pragmatic theory and praxis into dialogue with contemporary psychodynamic ideas, practitioners, and clinical issues. Generally considered as a historical footnote to psychoanalysis, the chapters in this volume demonstrate pragmatism's continued relevance for contemporary thought. Not only does pragmatism share many of the values and sensibilities of contemporary psychodynamics, its rich philosophical and theoretical emphasis on active meaning making and agentic being in the world complements and extends current thinking about the social nature of self and mind, how we occupy space in the world, non-linear development, and processes of communication.